Progressive Thinning of Visual Motion Area in Lower Limb Amputees - Jiang, Guangyao; Li, Chuanming; Wu, Jixiang; Jiang, Tianzi; Zhang, Yi; Zhao, Lu; Evans, Alan C.; Li, Lei; Ran, Shuhua; Yin, Xuntao; Wang, Jian (Frontiers in Human Neuroscience, 2016)
Accumulating evidence has indicated that amputation or deafferentation of a limb induces functional or structural reorganization in the visual areas. However, the extent of the visual areas involved after lower limb amputation remains uncertain. In this investigation, we studied 48 adult patients with unilateral lower limb amputation and 48 matched healthy controls using T1-weighted magnetic resonance imaging. Template-based regions of interest analysis was implemented to detect the changes of cortical thickness in the specific visual areas. Compared with normal controls, amputees exhibited significantly lower thickness in the V5/middle temporal (V5/MT+) visual area, as well as a trend of cortical thinning in the V3d. There was no significant difference in the other visual areas between the two groups. In addition, no significant difference of cortical thickness was found between patients with amputation at different levels. Across all amputees, correlation analyses revealed that the cortical thickness of the V5/MT+ was negatively correlated to the time since amputation. In conclusion, our findings indicate that the amputation of unilateral lower limb could induce changes in the motor-related visual cortex, and provide an update on the plasticity of the human brain after limb injury.